Introduction to Computer Graphics Using OpenGL and Java - Lehn, Karsten; Gotzes, Merijam; Klawonn, Frank (Cham : Springer International Publishing : Imprint: Springer, 2023)
A basic understanding of the key techniques in computer graphics can open the door to this exciting field and its many applications, including for video games and for augmented and virtual reality. This easy-to-follow textbook and reference introduces the fundamental concepts of computer graphics, integrating both technical background and theory with practical examples and applications throughout. Thoroughly revised and updated, this new edition continues to present a user-friendly approach to creating images and animations, complementing the expanded coverage of topics with usage of example programs and exercises. Topics and features: Contains pedagogical tools, including easy-to-understand example programs and end-of-chapter exercises Presents a practical guide to basic computer graphics programming using the Open Graphics Library (OpenGL) and the widely used Java programming language Includes new and expanded content on the OpenGL graphics pipelines, shader programming, drawing basic objects using the OpenGL, three-dimensional modelling, quaternions, rasterisation, antialiasing and more Supplies complete Java project examples as supplementary material This reader-friendly textbook is an essential tool for second-year undergraduate students and above, providing clear and concise explanations of the basic concepts of computer graphics. It will enable readers to immediately implement these concepts using the OpenGL and Java (with only elementary knowledge of the programming language). Prof. Dr.-Ing. Karsten Lehn works at the Faculty of Information Technology at Fachhochschule Dortmund, University of Applied Sciences and Arts. Prof. Dr. Merijam Gotzes is teaching at Hamm-Lippstadt University of Applied Sciences. Prof. Dr. Frank Klawonn is head of the Data Analysis and Pattern Recognition Laboratory at the Ostfalia University of Applied Sciences and heads the Biostatistics Research Group at the Helmholtz Centre for Infection Research.
Foreword to the Third Edition -- Acknowledgement -- 1. Introduction -- 2. the Open Graphics Library (OpenGL) -- 3. Basic Geometric Objects -- 4. Modelling Three-Dimensional Objects -- 5. Geometry Processing -- 6. Grey Scale and Colour Representation -- 7. Resterisation -- 8. Visibility Considerations -- 9. Lighting Models -- 10. Textures -- 11. Special Effects and Virtual Reality -- Appendix A: Web References -- Index.
Keywords: Computer graphics; Computer science; Programming languages (Electronic computers).; Computer programming; Computer Graphics; Computer Science; Programming Language; Programming Techniques